Research on Teaching and Learning Mathematics at the Tertiary Level State-of-the-art and Looking Ahead - Biza, Irene; Giraldo, Victor; Hochmuth, Reinhard; Khakbaz, Azimehsadat; Rasmussen, Chris (ICME-13 Topical Surveys,, 2016)
This topical survey focuses on research in tertiary mathematics education, a field that has experienced considerable growth over the last 10 years. Drawing on the most recent journal publications as well as the latest advances from recent high-quality conference proceedings, our review culls out the following five emergent areas of interest: mathematics teaching at the tertiary level; the role of mathematics in other disciplines; textbooks, assessment and students' studying practices; transition to the tertiary level; and theoretical-methodological advances. We conclude the survey with a discussion of some potential directions for future research in this new and rapidly evolving domain of inquiry.